Value of Loss Load Analysis of Java-Bali System Based on Macro Economic Data - Christina Purwaningsih; Sarjiya Sarjiya; Yusuf Susilo Wijoyo (Forum Pendidikan Tinggi Teknik Elektro Indonesia (FORTEI), 2020)
Industrial and business sectors have big influence to gross domestic product in some regions (GDP). Beside that, GDP is influenced by electricity consumption. That statement is the reason why value of loss load (VOLL) had to be calculated. This research calculates VOLL for getting the value of outage cost, efficiency and productivity industrial and business sector in each Area Pengaturan Beban (APB) and in entire Java-Bali region. VOLL is calculated by macroeconomic analysis because this method has more time efficiency than survey analysis. VOLL forecasting in 2016-2023 are calculated too in this research. After that, the outage cost forecasting in hierarchical level 1 (HL 1) can be gotten if expected energy not supplied (EENS) from HL 1 is calculated. Before EENS calculation is held, analysis of another reliability indices such as loss of load expectation (LOLE) and loss of load probability (LOLP) were calculated. The calculation results show that VOLL in 2017 is 35,100.67 Rp/kWh and EENS in HL 1 is 7.25 MWh. Total outage cost from calculation is 289 million rupiahs.